Proses Pengumpulan Data Dan Keakuratan Aplikasi Transfermarkt Sebagai Acuan Dari Harga Transfer Pemain Sepakbola Dunia - Mahardika Paramarta Laia; Risman Muhammad Hafidz; Melisa Dwi Hestiani; Ahmad Suhendri; Aries Saifudin (CV. Multi Kreasi Media, 2023)
Currently, the market price for football players is experiencing an uncorrected price increase, especially for young players because there is no official/standard reference for player prices from FIFA as the highest body that oversees world football, therefore Axel Springer created the Transfermarkt site which has a price reference feature. soccer players, even though this site is not under the auspices of FIFA, many clubs use this site to buy/sell players. the working system of this site is very simple, they let their members discuss / create opinions to assess a player's market based on important data as a benchmark, such as age, number of matches, rating for each match, goals etc. After that, transfermarkt makes the final price value based on discussion from site members. Researchers from the London School of Economics and Political Science state that the football player transfer rumors from transfermarkt are highly accurate. This research aims to determine the impact of team status on the market value of professional soccer players, transfer fees on the market value of professional soccer players and salary costs on the market value of professional soccer players. This research is qualitative research with a total of 105 professional soccer players as respondents. Data obtained from transfermarkt site. The sampling technique used was purposive sampling. The data used is secondary data. The research results show that team status has a positive and significant impact on the market value of professional soccer players, transfer fees have a positive and significant impact on the market value of professional soccer players and salary costs have a positive and significant impact on the market value of professional soccer players.